The Implementation of Learning the Book of Matan Jazariyah in Increasing Fluency in Reading the Qur'an Madrasah Isti'dadiyah Darul Falah - Nikmah, Lutfiatun; Ekhwanuddin, Ekhwanuddin; Wijaya, Adi (International Journal on Advanced Science, Education, and Religion, 2025)
The ability to read the Al-Qur'an of the Class II students of Madrasah Isti'dadiyah Darul Falah (MIDA) Seputih Banyak, Central Lampung is still considered poor. In reality, in order to be able to read the Koran fluently and tartly, there needs to be gradual and in-depth learning. Therefore, the step taken by the Islamic boarding school is to hold a study of the Jazariyah book so that the students are able to master the rules of Tajwid and Makhorijul letters. So, with this research, it is hoped that we will be able to find out how the learning of the Jazariyah book is implemented in Class II Santri at Madrasah Isti'dadiyah Darul Falah (MIDA) Seputih Banyak, Central Lampung. The method used in this research is qualitative field research. Meanwhile, the data collection technique uses data collection through observation, interviews and documentation. The research results show that the implementation of book learning Matan Jazariyah Improving the Understanding of Tajweed in Class II Students of Madrasah Isti'dadiyah Darul Falah (MIDA) Seputih Banyak, Central Lampung is carried out in two indicators, namely Fluency in Reading the Al-Quran and accuracy in Tajweed. The indicator of fluency in reading the Al-Quran is that students who have the ability to read the Al-Qur'an well have more opportunities than ustadz to be able to continue memorizing the next letter. However, for students whose ability to read the Qur'an is not very good, they are not allowed to continue memorizing until they have really improved the quality of their reading of the Qur'an. Then the indicator of accuracy in the tajwid is that the learning material for the science of tajwid taught to the santri comes purely from the material of the Jazariyah Book, clarified through the sharah of the Jazariyah Book and has been adapted to the students' abilities, so that students who are not very familiar with the science of tajwid will be greatly helped by this material